Pengembangan Literasi Anak Pada Program Teras Baca Di Desa Renah Semanek - Fadilah, Fadilah; Andara, Aulia; Afrilia, Dea; Rosida, Rosida; Nata, Edwin Triadi; Andreani, Mesi; Rosyid, Arif Abdul; Syaputra, Ramadhan; Husna, Lailatul; Maryam, Riskianti Astuti; Naimah, Rifngatun (Pakis Journal Institute, 2024)
The research data collection method is carried out using dedication and observation, which aims to research and help the community, and to explore social problems and phenomena and develop a specific understanding of a phenomenon. The collection location is in Renah Semanek village, Karang Tinggi Sub-District, Central Bengkulu District. The variable underlying this research is reading literacy covering early childhood and adolescence. The subjects in this research are early childhood and teenagers. The results of this service program are increased motivation in learning. as well as their speaking and reading abilities. This proves that this program has a very good impact. Apart from that, this program also has a positive impact on several aspects such as social and educational aspects for both the children and volunteers involved. Maximum efforts were made in this program and supported by various parties, the results of this service achieved 85% success which can be seen from the completion of the provision of learning platforms, namely reading terraces and procurement of books. Providing reading terraces to the community is also an effort to increase the willingness to read and will have an impact on improving the standard of living of village communities. Apart from that, of course additional good reading is needed to broaden the insight and knowledge of village communities.